Prospective Randomized Multicenter Comparison of the Clinical Outcomes of V4c and V5 Implantable Collamer Lenses: A Contralateral Eye Study - Takashi Kojima; Yoshihiro Kitazawa; Tomoaki Nakamura; Masahide Takahashi; Kazutaka Kamiya; Kazuo Ichikawa; Akihito Igarashi; Kimiya Shimizu (Journal of Ophthalmology)
Purpose. To compare the visual and refractive outcomes and night vision performance questionnaire results between V4c and V5 implantable Collamer lenses in a prospective, randomized, multicenter study. Settings. Four refractive surgery centers. Design. Prospective randomized multicenter single-masked comparative study. Methods. Twenty-three patients were enrolled in this study. A conventional V4c model (EVO Visian ICL) was implanted in one eye, and a V5 model (EVO+ Visian ICL), which has a larger optic diameter than the V4c model, was implanted in the contralateral eye. The uncorrected distance visual acuity (UDVA) and corrected distance visual acuity (CDVA) were evaluated before and 6 months after surgery. At 6 months after surgery, a questionnaire on night vision disturbances was administered. The efficacy, safety, and predictability of the two implanted ICL models were compared. Results. There were no significant differences in the postoperative UDVA and CDVA between the two ICL models. The mean efficacy indexes for the V4c and V5 lenses were 1.16 ± 0.22 and 1.03 ± 0.23, respectively. The mean safety indexes of the V4c and V5 lenses were 1.21 ± 0.20 and 1.19 ± 0.20, respectively. The night vision performance questionnaire revealed that 7 patients (37%) noticed a difference in visual performance between the eyes, and all of them reported that they could see better at night with the V5-implanted eye compared with the V4c-implanted eye. Conclusion. The V4c and V5 ICL models achieved similar visual and refractive outcomes, whereas the V5 model showed a possible advantage in reducing night vision disturbances.